Participatory Geographic Information System: citizen science approach in Potiguara Indigenous Land of Paraíba - Brazil - Oliveira, Renata Guimarães; Iwama, Allan Yu; Gonçalves, Alicia Ferreira; Galdino, Nathan Tuxaua; Braga, Júlia Oliveira; Rodrigues Neta, Edithe; Garcia, Jade Rosa Hilario; Lima, Elias Gerônimo de; Alfredo, Ismael dos Santos; Andrade, Maristela (Sustainability in Debate, 2025)
Indigenous culture and ancestry have been historically threatened in the Potiguara Indigenous Territory in Paraíba, generating conflicts within its territory. The Territorial and Environmental Management Plan (PGTA) is a fundamental tool for addressing these conflicts. This article integrated a citizen science approach with a social cartographic map in a participatory Geographic Information System (PGIS) to identify the social-environmental impacts observed by the Potiguara, in defence of indigenous and traditional territories. PGIS workshop, along with guided tours and drone overflights, mapped together 29 Potiguara indigenous aspects of cultural, social, environmental, and political themes, identifying: 68 places related to cultural aspects; and 27 points of potential/threats. The citizen science approach connected with PGIS was essential for the territorial claim of the Potiguara, highlighting five key elements for its applicability: (1) creating a trustful environment; (2) recognizing local and traditional knowledge; (3) analyzing conflicts across temporal and spatial scales; (4) promoting empowerment in the use of geotechnologies; and (5) including Potiguara intergenerational participation in the identification and monitoring of social-environmental impacts.